"PEDAGOGICAL CONFLICTOLOGY IN THE DEVELOPMENT STRATEGY OF PRESCHOOL EDUCATIONAL ORGANIZATIONS: THEORY, PRACTICE AND PROBLEMS" - Zulpukorova Parvina Ruzmat qizi (TADQIQOTLAR, 2025)
Annotation This  article  covers  the  theoretical  and  practical  aspects  of  pedagogical conflictology. It provides a detailed analysis of the types of conflicts that arise in the pedagogical process, their causes, methods of identification and diagnosis, strategies for  preventing  and  resolving  conflicts.  It  also  demonstrates  the  effective  use  of pedagogical  conflictology  through  practical  examples  from  preschool  and  school educational  environments.  The  article  provides  practical  recommendations  for understanding and resolving pedagogical conflicts and is intended as a useful guide for pedagogical personnel, parents, and specialists working in the field of education.